Energy and Environmental Analysis of Membrane-Based CH4-CO2 Replacement Processes in Natural Gas Hydrates - Beatrice Castellani; Alberto Maria Gambelli; Andrea Nicolini; Federico Rossi (Energies, 2019)
Natural gas hydrates are the largest reservoir of natural gas worldwide. This paper proposes and analyzes the CH4-CO2 replacement in the hydrate phase and pure methane collection through the use of membrane-based separation. The investigation uses a 1 L lab reactor, in which the CH4 hydrates are formed in a quartz sand matrix partially saturated with water. CH4 is subsequently dissociated with a CO2 stream supplied within the sediment inside the reactor. An energy and environmental analysis was carried out to prove the sustainability of the process. Results show that the process energy consumption constitutes 4.75% of the energy stored in the recovered methane. The carbon footprint of the CH4-CO2 exchange process is calculated as a balance of the CO2 produced in the process and the CO2 stored in system. Results provide an estimated negative value, equal to 0.004 moles sequestrated, thus proving the environmental benefit of the exchange process.